1986
DOI: 10.1063/1.451857
|View full text |Cite
|
Sign up to set email alerts
|

A method of calculating electron correlations for large molecules involving C, N, and H atoms

Abstract: A way of calculating the electron correlation energy for the ground state of large organic molecules is presented. It is demonstrated that various contributions to the correlation energy may be described by simple analytic expressions. In the case of interatomic correlations, they depend only on the bond length, its kind (e.g., σ or π bond) and the atoms involved in the bonding. Intraatomic correlations for a given atom are shown to be determined by its total charge and the fraction of p electrons. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…in titanium or vanadium oxides) are even stronger correlated than e g electrons in the RMnO 3 or RNiO 3 perovskites. This resembles the situation in molecular bonds in sp systems, with π bonds being always stronger correlated than σ bonds [17]. A second class of correlated insulators, so-called charge transfer insulators, arises when the oxygen states are within the gap between the two Hubbard subbands [18].…”
Section: Degrees Of Freedom In Transition Metal Oxidesmentioning
confidence: 99%
“…in titanium or vanadium oxides) are even stronger correlated than e g electrons in the RMnO 3 or RNiO 3 perovskites. This resembles the situation in molecular bonds in sp systems, with π bonds being always stronger correlated than σ bonds [17]. A second class of correlated insulators, so-called charge transfer insulators, arises when the oxygen states are within the gap between the two Hubbard subbands [18].…”
Section: Degrees Of Freedom In Transition Metal Oxidesmentioning
confidence: 99%
“…It is known from the pioneering work of Pauling, Mulliken, Coulson and other authors [8,9,10], that bond order and molecular bond length are strongly correlated. In this sense our work is somewhat related to the work of Fulde et al [11,12], where an analytical model of molecular correlation energies based on bond lengths was proposed.…”
Section: Introductionmentioning
confidence: 89%
“…These parameters are fixed as follows for the Cu-O plane. Our previous studies [15] have demonstrated that atomic values of the Coulomb interaction have to be used in order to obtain the correct interatomic correlation energies for bonds formed by s and p electrons. The same applies in principle to d electrons.…”
Section: Resultsmentioning
confidence: 99%